Gender difference in tooth autotransplantation with complete root formation: a retrospective survey. (26th February 2013) - Yoshino, K.; Ishizuka, Y.; Sugihara, N.; Kariya, N.; Namura, D.; Noji, I.; Mitsuhashi, K.; Kimura, H.; Fukuda, A.; Kikukawa, I.; Hayashi, T.; Yamazaki, N.; et al.
<x xml:space="preserve">Abstract</x> Summary Gender‐related risk factors in the survival of transplanted teeth with complete root formation have not yet been identified. The purpose of this study was to investigate gender differences in tooth autotransplantation at dental clinics. We asked participating dentists to provide information on transplantations they had undertaken from 1 January 1990 to 1931 December 2010. The data were screened to exclude patients who underwent more than one transplantation, smokers or those whose smoking habits were unknown, patients under 30 or who were 70 years old and over, cases where the transplanted teeth had incomplete root formation or multiple roots and those with fewer than 20 present teeth post‐operation. We analysed 73 teeth of 73 males (mean age, 47·2 years) and 106 teeth of 106 females (mean age, 45·3 years) in this study. The cumulative survival rate and mean survival time were calculated using the Kaplan–Meier method. The cumulative survival rate for males was 88·3% at the 5‐year mark, 64·8% at 10 years and 48·6% at 15 years; for females, it was 97·2% at the 5‐year mark, 85·9% at 10 years and 85·9% at 15 years. A log‐rank test indicated the difference between males and females to be significant (P = 0·011). There was also a significant difference in the main causes for the loss of transplanted teeth: males lost more transplanted teeth due to attachment loss than females (P < 0·05). These results indicate that males require more attention during the autotransplantation process, particularly at the stage of pre‐operation evaluation and that of follow‐up maintenance.